SAT0164 Adverse drug reactions due to disease modifying drugs in patients with incident rheumatoid arthritis. (12th June 2018) - Rosales Rosado, Z.; Freites NÚÑEZ, D. D.; Lajas Petisco, C.; Pato Cour, E.; Mateos, León; Alcázar, L. Abásolo
Abstract : Background: There is a well-known risk of developing adverse drug reactions (ADR) in rheumatology due, mainly, to the Disease Modifying Antirheumatic Drugs (DMARD) used. There is no doubt about their efficacy in Rheumatoid Arthritis (RA), but it is necessary to increase our knowledge of their ADR, especially those that lead to discontinuation Objectives: To describe the incidence and characteristics of ADR related with DMARD in patients with incident RA as well as the factors involved in their development Methods: Observational retrospective longitudinal study between April 15th 2007 and December 31st 2016. Inclusion criteria : patients diagnosed with RA between April 15th 2007 and June 31st 2011 followed until December 31st 2016 whom started any DMARD. Primary endpoint : development of an ADR that required discontinuation of the DMARD (moderate: discontinuation; severe: discontinuation with hospitalization or death). Co-variables : sociodemographic; clinical and therapy. Statistical analysis : incidence rates of discontinuation (IR) per 100 patient-years were estimated using survival techniques with their respective 95% confidence interval [CI]. Comparisons between associated factors were run by Cox bivariate and multivariate regression models. Results were expressed by hazard ratio (HR) and [CI] Results: We included 1054 courses of DMARD treatment in 405 patients (2277.9 patient-years). 78.3% were women with a mean age at diagnosis of 57±15 years. During follow-up, 16.3% of patients were taking biological DMARD, 73.3% were using monotherapy and 89% were taking corticoids. There were 369 ADR in 212 patients, 88.9% moderate. Gastrointestinal was the most frequent cause of ADR (26.3%), followed by infections (12.2%). IR are shown in table 1 and the multivariate analysis in table 2. Regarding type of DMARD, Abatacept had the highest risk of ADR development (HR:4.9[2.1–11.2]) compared to the other drugs followed by Gold (HR:1.6[1–2.6]) and Leflunomide (HR:1.4[1.1–1.9]). Methotrexate was the safest drug compared with the others (0.6[0.5–0.8]) Conclusions: The IR of ADRwas 16.2%, being similar in all age categories. Gastrointestinal was the main cause of ADR followed by infections. We have found differences in discontinuation rates among DMARD due to ADR, being Abatacept, Gold and Leflunomide the drugs with the highest risk. Methotrexate had a lower risk of ADR compared to other DMARD. Caution should be taken in patients receiving combined therapy and with certain comorbidities Disclosure of Interest: None declared